2018
DOI: 10.1002/rth2.12113
|View full text |Cite
|
Sign up to set email alerts
|

Immigration, region of origin, and the epidemiology of venous thromboembolism: A population‐based study

Abstract: BackgroundVenous thromboembolism (VTE) epidemiology has been mainly studied in populations largely of European ancestry.ObjectivesTo assess the epidemiology of VTE in immigrants to Ontario, Canada.Patients/MethodsWe conducted a population‐based retrospective cohort study using linked health‐care and administrative databases. We included 1 195 791 immigrants to Ontario and 1 195 791 nonimmigrants, matched on age, sex, and place of residence. The main exposure was ethnicity according to world region of origin, u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…The use of oral contraceptives, as well as hormone replacement therapies, pregnancy, the immediate postpartum state, and obstetrical complications are all risk factors for these complications[ 119 ]. There are many such factors, however, including ethnicity[ 120 ]. Despite the many contributing factors, pregnant women on APs have been shown to be at significantly higher risk for venous thromboembolism than pregnant women in the general population[ 121 , 122 ].…”
Section: Drug Side Effectsmentioning
confidence: 99%
“…The use of oral contraceptives, as well as hormone replacement therapies, pregnancy, the immediate postpartum state, and obstetrical complications are all risk factors for these complications[ 119 ]. There are many such factors, however, including ethnicity[ 120 ]. Despite the many contributing factors, pregnant women on APs have been shown to be at significantly higher risk for venous thromboembolism than pregnant women in the general population[ 121 , 122 ].…”
Section: Drug Side Effectsmentioning
confidence: 99%
“…Venous thromboembolism (VTE) presents as deep vein thrombosis (DVT) or pulmonary embolism (PE) and affects approximately 1 to 2 per 1000 people per year 1,2 . While untreated PE can be fatal, the risk of death decreases with treatment, and mortality rates have declined over the past 2 decades 3,4 .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the ndings are not readily generalizable to ACLR with other graft types, such as quadriceps tendon, bone-patellar-bone graft, or allograft. The ndings may be ethnicity-speci c. However, previous studies have not found signi cant difference in tendency to VTE between middle eastern and white ethnicities [25]. Also, the lack of access to some data such as the length of surgery might have hidden some potential sources of bias.…”
Section: Discussionmentioning
confidence: 83%